Modeling the Africa Diaspora Pension Fund: likely financing instrument for Africa's development infrastructure - Mazibuko, Patras (Research of GSB, 2018)
The case study research sought to investigate and establish the attitude of the Africa diaspora community, mainly associated with the University of Cape Town, towards the modeling of a diaspora pension fund as a likely instrument for the financing of the continent's development infrastructure. The case study further sought to test, using chi-square and logistic regression, whether the independent variables of age, gender and education have an effect on the willingness/support of the members of the diaspora in the establishment of the diaspora pension fund for the financing of the continent's infrastructure. The results show that members of the sampled diaspora community support the modeling and also showed their willingness to be part of the diaspora pension fund and to have part of their pension contributions invested for the financing of the development infrastructure. The resulting model shows that males, who are middle-aged and well-educated, are more likely to be in support of the modeling of the diaspora pension fund as a likely instrument for financing the continent's development infrastructure. The results show that when modeling the diaspora pension fund factors such as age, education, gender, remaining years towards retirement, governance, corruption, regulatory issues, and the rule of law and the infrastructure of investment portfolio diversification have to be taken into account as they affect the likelihood of support amongst the diaspora community. The research will help policy makers, global pension funds, governments in Africa, and the bigger community of the Africa diaspora in assessing the feasibility of commercialising the diaspora pension fund as an innovative financing instrument.